The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1017/s0033291718002520
|View full text |Cite
|
Sign up to set email alerts
|

Trauma-associated anterior cingulate connectivity during reward learning predicts affective and anxiety states in young adults

Abstract: In a young adult sample, two pathways linked the impact of trauma on reward-learning networks with higher v. lower negative affective and anxiety symptoms. The disconnection between vACC and regions implicated in decision-making and self-referential processes may reflect aberrant regulatory but appropriate self-focused mechanisms, respectively, conferring risk for v. resilience against negative affective and anxiety symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 70 publications
2
11
0
Order By: Relevance
“…The thalamus and insula are two key components of the reward neurocircuitry which links motivation with complex behaviors [76]. Auditory participats in the reward process with acoustic stimuli [77], and anxiety disorders often exert negative effect on the reward network [78]. More work is needed to determine how SNHL contributes to reward process and its correlation with SNHL-induced anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…The thalamus and insula are two key components of the reward neurocircuitry which links motivation with complex behaviors [76]. Auditory participats in the reward process with acoustic stimuli [77], and anxiety disorders often exert negative effect on the reward network [78]. More work is needed to determine how SNHL contributes to reward process and its correlation with SNHL-induced anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to changes in regional brain activity, emotional perception may also alter the interregional functional connectivity (FC) as well as the brain network topology. At the connectivity level, studies have employed FC analysis and investigated reorganized FC induced by emotional processing (Anticevic et al, 2011; Kim et al, 2011; Klapwijk et al, 2013; Eckstrand et al, 2018; Ewbank et al, 2018). At the network level, the recent advancement in computational approaches, especially graph-theoretical analysis, has provided the means to characterize the brain network topology (Rubinov and Sporns, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The FC between IPL and frontal regions is implicated in attention control and decision‐making processes (Chen et al, 2013), the FC between IPL and visual regions subserves visual attentional processing (Numssen, Bzdok, & Hartwigsen, 2021), and the FC between insula and STG is involved in internal‐focused attention (Jang et al, 2018). Previous studies have found reduced FCs of the IPL with visual regions (Philip, Kuras, et al, 2013) and ACC (Eckstrand et al, 2019) were related to early life trauma exposure. Of note, CM‐related reduced FC between the IPL and dorsolateral PFC during sustained attention was moderated by SNP rs3800373 (Hart et al, 2017).…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have found reduced FCs of the IPL with visual regions (Philip, Kuras, et al, 2013) and ACC (Eckstrand et al, 2019) were related to early life trauma exposure. Of note, CM-related reduced FC between the IPL and dorsolateral PFC during sustained attention was moderated by SNP rs3800373 (Hart et al, 2017).…”
Section: Altered Tom Connectome Related With CMmentioning
confidence: 81%
See 1 more Smart Citation